Intervention effect of Malus pumila leaf flavonoids on senna‐induced acute diarrhea in BALB/c mice. Issue 5 (5th April 2020) - Yi, Ruokun; Tian, Yu; Tan, Fang; Li, Wenfeng; Mu, Jianfei; Long, Xingyao; Pan, Yanni; Zhao, Xin
Abstract: The Malus pumila leaves are used as a kind of tea drink in China, and there are abundant flavonoids in the leaves of Malus pumila . In this study, BALB/c mice received senna extract solution via gavage, which induced acute diarrhea, and the interventive effect of Malus pumila leaf flavonoids (MPLF) was observed. The results showed that MPLF decreased the diarrhea index, and MPLF also decreased the capillary permeability in the abdominal cavity of mice. The result of serum cytokine detection indicated that MPLF decreased the levels of inflammatory cytokines, including interleukin 6 (IL‐6), interleukin 12 (IL‐12), and tumor necrosis factor alpha (TNF‐α). The results of quantitative polymerase chain reaction (qPCR) indicated that diarrhea decreased the mRNA and protein expression of aquaporin‐3 (AQP3) in the jejunum and aquaporin‐4 (AQP4) in the ileum, which were inhibited by MPLF. By high performance liquid chromatography (HPLC), MPLF mainly contains 10 flavonoids, which are rutin, hyperoside, isoquercitrin, taxifolin, quercitrin, hesperidin, myricetin, baicalin, neohesperidin dihydrochalcone and quercetin, the synergistic effect of these components plays an antidiarrhea role in MPLF. Therefore, MPLF achieved good antidiarrheal effect, which was better than that of the commonly used montmorillonite powder at the same concentration. MPLF is a natural raw material for functional food with an antidiarrheal effect. Abstract : Malus pumila leaf flavonoids inhibited senna‐induced acute diarrhea in BALB/c mice through up‐regulation AOP3 mRNA and protein expression in jejunum tissue and AQP4 expression in ileum tissue.